Influence of the synthesis conditions on the incorporation of B and the acidity in B-MCM-41 materials - Vaschetto, Eliana Gabriela (2016)
B-MCM-41 type nano-structured materials were prepared by direct hydrothermal synthesis. The time of hydrothermal treatment, the Si/B initial molar ratio and the nature of the hydroxide source in the synthesis process were analyzed. All the materials were characterized by XRD, N2 adsorption, TEM, SEM, ICP-OES, FT-IR and adsorption of pyridine coupled to FT-IR spectroscopy. The role of hydroxide source is essential to achieve the incorporation of boron in the mesoporous structure. The relationship between the Boron content in the synthesis gel, the degree of introduction of tetra-coordinated B into the framework, the formation of nest silanols and the relative density of the acidic sites have been discussed. We could corroborate that hydroxyl groups present in silanol nests are the direct responsible of the moderate Brønsted acidity of our materials. The enhancement in the density of acidic nest silanols was reached by increasing the B content in the mesoporous structure. Finally, the use of NH4OH, as hydroxide source, Si/B initial molar ratio of 10 and 20 and a hydrothermal treatment of 6 days resulted the optimum synthesis conditions to obtain the highest framework B incorporation and more abundant moderate Brønsted sites (silanol nests), thus improving the potential catalytic properties of these materials.